High Seroprevalence Against Typhus Group and Spotted Fever Group Rickettsiae in Rural Indigenous Populations of Peninsular Malaysia - Dennis, Tappe; Yvonne, Gross; Romano, Ngui; Jessica, Rauch; Sun, Tee Tay; Yvonne Ai, Lian Lim (Mary Ann Libert, Inc., 2019)
Rickettsioses of the typhus group (TG) and spotted fever group (SFG) are emerging bacterial infections worldwide, especially in the tropics. Only a few studies on these pathogens and their respective clinical diseases have been conducted in Malaysia. Here, we performed a seroprevalence study among 544 healthy, afebrile indigenous people (Orang Asli) from peninsular Malaysia for TG and SFG rickettsioses in nine rural and peri-urban settlements. The study population encompassed children, adolescents, and adults. The overall seroprevalence of rickettsiosis in the Orang Asli was 48.5%, with 27.9% seroprevalence against TG rickettsiae and 20.6% seroprevalence against SFG rickettsiae. In 7.9% of the study participants, antibodies against both rickettsial groups were found. The highest seropositivity rates against TG and SRG rickettsiae were detected in young children and adults. Overall, there were no gender differences. Seroprevalences were similar among inhabitants of different settlements, except for two localities. More studies are needed to shed more light on the ecology and risk factors for TG and SFG rickettsioses in Malaysia.